De-Location "Indipendence:" The Discourse on Southeast Asian Indipendent Cinema (Cinéma & Cie. Film and Media Studies Journal, 2013)
This essay examines the ways Southeast Asian Independent Cinema can be located – or, perhaps, de-located –, departing from traditional concepts of film studies, by examining the discourse on this cinematic movement as it is shaped by local and foreign voices. The paper focuses on the nexus of independence, political involvement and regionalism and asks how these meanings are negotiated in their transfer from various previous concepts of cinematic independence and alternativeness into the local context. As Southeast Asian Independent Cinema challenges conventional notions of film studies (the frame of national cinemas; the binary system of Hollywood vs. World Cinema; and the pre-digital cinematic apparatus), it presents an opportunity to rethink and expand traditional concepts and the underlying epistemologies in an innovative, non-Eurocentric way.